Estimation and management of shrimp processing waste in organised shrimp processing sector in India: Opportunities and challenges - C. G. Joshy; K. Elavarasan; V. Renuka; B. Madhusudana Rao; K. V. Premdev; A. A. Zynudheen; Ninan, George (Indian Journal of Fisheries, 2023)
This study was conducted to estimate the magnitude of processing waste produced in theorganised shrimp processing sector of India in order to assess the opportunities availablefor its utilisation. The estimation of magnitude of shrimp processing waste was based onsecondary data and its management was based on primary data collected through surveysat processing plants. The organised shrimp processing sector in India generated a largevolume of shrimp processing waste at a growth rate of 12% during 2000-2018. The quantityof shrimp processing waste generated ranged from 1.2 to 4.6 lakh t, which can be utilisedto produce 6712 to 27453 t of chitin alone. However, our study indicated that 75% of thetotal waste generated remained either unused or managed unscientifically, even when thereis huge demand for chitin and its derivatives in the domestic as well as in the internationalmarket. The case studies from chitin producing plants revealed that some costs wereincurred in the procurement of shrimp processing waste as a secondary raw material for theproduction of chitin. Thus forming a link between shrimp processing plants and chitin and itsderivatives producing plants would improve the supply of quality raw material and improveutilisation of processing wastes. The number of chitin and its derivatives producing plantsare too few in India to fully accommodate the large volume of shrimp processing wastegenerated every year. Therefore, infrastructure development in the chitin and associatedindustry with active support from government organisations to overcome the burden of initialinvestment is needed urgently, which can in turn encourage entrepreneurship developmentin the sector for diversified applications.Keywords:Chitin, Chitosan, Glucosamine hydrochloride,Growth rate, Waste utilisation